New Trends in Ion Exchange Studies - Karakuş, Selcan (IntechOpen, 2018)
This book covers new systems in technology that have developed our knowledge of ion exchange. This book discusses ion exchange resins to enhance cell growth; anion exchange membrane; nanosystems in ion exchange and ion exchange in environmental applications. The ion exchange system is used in bionanotechnology, cosmetic industry and water treatment.